1990
DOI: 10.1126/science.2300816
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of HIV Infection in AZT-Treated SCID-hu Mice

Abstract: The SCID-hu mouse, engrafted with human hematolymphoid organs, is permissive for infection with the human immunodeficiency virus (HIV). This mouse model was used to test compounds for antiviral efficacy. Two weeks after infection with HIV, 100 percent (40/40) of SCID-hu mice were positive for HIV by the polymerase chain reaction. When first treated with 3'-azido-3'-deoxythymidine (AZT), none (0/17) were HIV-positive by this assay. However, AZT-treated SCID-hu mice did have a few infected cells; after AZT treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(93 citation statements)
references
References 23 publications
2
91
0
Order By: Relevance
“…Amplified DNA was stored at -20°C until use. The template capability of purified DNA was verified by performing a PCR using /3-globin primers (19 (17) at 37°C. The filters were exposed to Kodak XAR film for 5-7 days at -70°C.…”
Section: Methodsmentioning
confidence: 99%
“…Amplified DNA was stored at -20°C until use. The template capability of purified DNA was verified by performing a PCR using /3-globin primers (19 (17) at 37°C. The filters were exposed to Kodak XAR film for 5-7 days at -70°C.…”
Section: Methodsmentioning
confidence: 99%
“…E. Osterhaus. Fax + 31 10 4365145, e-mail Osterhaus@viro.fgg.eur.nl haematopoietic tissue into SCID mice (Mosier et al, 1991;Namikawa eta]., 1988); subsequently, the activated human graft is infected with HIV-1. In these models it was demonstrated that polyclonal hyperimmune globulins from seropositive donors (HIVIG), a monoclonal antibody (MAb) directed against the V3 loop on HIV-1 gp120 and 3'-azido-2',3'-dideoxythymidine (AZT) inhibited the replication of T cell line-adapted (TCLA) HIV-1 strains (Safrit et al, 1993;Shih et at., 1991;McCune et al, 1990). In infected individuals HIV-I has been shown to replicate predominantly in activated macrophages and T lymphocytes resulting in high virus loads in lymphoid organs (Embretson et al, 1993;Pantaleo et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…HLA matching and T cell depletion ofthe donor graft are also useful adjuncts to mitigate development of life-threatening graft versus host disease (GVHD) which may occur during graft rejection (1,2). When applied appropriately, these procedures have been used to achieve chimerism between different species including humanmouse (4)(5)(6)(7)(8)(9)(10). Xenogeneic transplantation ofhuman HSC has also been reported in genetically deficient mice (5)(6)(7)(8)(9)(10) and in normal mice rendered tolerant by lethal irradiation (4).…”
mentioning
confidence: 99%
“…Tolerance oftransplanted allogeneic cells in clinical settings can be achieved using genetically immunodeficient donors/recipients (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Alternatively, immunocompetent recipients can be rendered immunotolerant by using immunosuppressive and/or cytoablative procedures, which may also serve to promote engraftment by donor HSC by eliminating recipient HSC which may compete for homing sites within the bone marrow (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). HLA matching and T cell depletion ofthe donor graft are also useful adjuncts to mitigate development of life-threatening graft versus host disease (GVHD) which may occur during graft rejection (1,2).…”
mentioning
confidence: 99%